On the issue of the object of crime committed with application of psychic coercion against the ownership - E. N. Barchatova (Сибирское юридическое обозрение, 2013)
The article deals with the problems of definition of object of crime committed with application of psychic coercion against the ownership. The author proposes to assign a subgroup object characteristic for the indicated type of crimes. This object includes the relations concerning the distribution and redistribution of material values as well as life, health, freedom, constitutional rights and freedoms of a human being.